2011
DOI: 10.1245/s10434-011-1893-y
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Pancreatic Fistula and the Risk Factors of Laparoscopy-Assisted Distal Gastrectomy for Early Gastric Cancer

Abstract: LADG can be performed safely in patients with EGC in terms of the low incidence of POPF. To decrease the risk of POPF, LADG should be performed cautiously in male patients with high body mass index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 29 publications
4
62
1
Order By: Relevance
“…However, neither after gastrectomy nor after pancreatic resection has evidence ASA score (n = 90) 0.2174 Pancreatic fistula after D2 gastrectomy 575 been presented to justify the routine use of such drains [21,22]. As shown in several other studies, we found that the dominating risk factor for POPF grade B and C was concomitant pancreatic resection, but determined no impact of BMI or splenectomy as in previous studies [10,11]. There was a minor effect of patient age on the risk of POPF.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…However, neither after gastrectomy nor after pancreatic resection has evidence ASA score (n = 90) 0.2174 Pancreatic fistula after D2 gastrectomy 575 been presented to justify the routine use of such drains [21,22]. As shown in several other studies, we found that the dominating risk factor for POPF grade B and C was concomitant pancreatic resection, but determined no impact of BMI or splenectomy as in previous studies [10,11]. There was a minor effect of patient age on the risk of POPF.…”
Section: Discussionsupporting
confidence: 49%
“…In 2005 the International Study Group of Pancreatic Fistula (ISGPF) divided POPF into three degrees of severity. This definition has gained general acceptance in the literature covering pancreatic surgery [9] and the latest Japanese publications that report on POPF after gastrectomy have accordingly used the ISGPF definition [10][11][12]. To our knowledge, there is no corresponding information from the Western hemisphere, when this standardized classification has been used to describe the outcome of D2 gastrectomy, with particular emphasis on the impact of bursectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies investigated the causes of POPF in total gastrectomy or laparoscopic gastrectomy. [8][9][10][16][17][18][19][20] However, this study aimed to identify the overall incidence and risk factors of POPF after various curative surgeries for gastric cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are few reports about POPF after curative gastrectomy for gastric cancer, especially about comparison between laparoscopic and open gastrectomy. [8][9][10] The purpose of this study is to evaluate the actual incidence and risk factors of POPF in both laparoscopic and open gastrectomy for gastric cancer during short concentrated two years in the experienced high volume center.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonically activated devices (USADs) have been suspected to be associated with this complication [1,2], since they are widely used for lymph node dissection during laparoscopic gastric cancer surgery, and cavitation generated from the blade in USADs may have a harmful effect on various biological tissues [3][4][5][6]. In this study, we analyzed the mechanical and biological effects of USADs with two different types of blade and addressed the question of whether USADs could be the direct cause of POPF after laparoscopic gastric cancer surgery.…”
Section: Introductionmentioning
confidence: 99%